Phytoplankton map - Idris, Nurul Syafinaz; Abu Seman, Nur Alya Farzana; Kamaruddin, Sharir Aizat; Roslani, Muhammad Akmal; Hashim, Aimie Rifhan (Universiti Teknologi Mara, Kedah, 2022)
Since they are net oxygen producers, phytoplankton contributes to the ocean's dissolved oxygen levels, which are necessary for fish, larger creatures, other plankton, and bacteria to breathe. Due to their importance for the earth, their distribution in our aquatic environment can be mapped. The objective of our innovation is to produce maps of phytoplankton. The name of our product is Phytoplankton Map. To date, there has not been any development of a phytoplankton map, especially in the Northern region of Malaysia, which gave extra advantages to our product. Phytoplankton Map will benefit many local, government and non-government users. Phytoplankton Map is consistent with the Sustainable Development Goals established by the United Nations SDG 14: "Life below water," SDG 2: "Zero hunger," SDG 3: "Good health and well-being," and SDG 13: "Climate action".